Surface to Groundwater Interactions beneath the City of Berlin: Results from 3D Models. (13th March 2019) - Frick, Maximilian; Scheck-Wenderoth, Magdalena; Schneider, Michael; Cacace, Mauro
Abstract : Knowing the thermal and hydraulic conditions below major urban centers is of increasing importance in the context of energy and water supply. With this study, focusing on the major urban center of Berlin, Germany, we aim to gain insights on the coupling of surface water bodies to the subsurface thermal and hydraulic field investigating shallow water to deep groundwater interactions. Therefore, we use a 3D structural model of the subsurface, constrained by all available data and observations, as a base for simulations of the coupled transport of fluid and heat. This model resolves the 3D configuration of the main geological units and thus enables us to account for related heterogeneities in physical properties. Additionally, we resolve surface water body geometries with newly available data. To assess how surface water bodies interact with the deeper groundwater at different depths in the model domain, the influence of different hydraulic boundary conditions is quantified, which indicates that the coupling of surface water bodies and groundwater strongly modifies predicted groundwater circulation. Consequently, changes in subsurface temperatures are also predicted, where lakes may account for temperature differences up to ±5°C and rivers could account for up to ±1°C visible at depths ≤-500 m.a.s.l. These differences are mainly connected to changes in the advective component of heat transport caused by the modifications of the hydraulic boundary condition. Pressure-driven heat transport is most efficient where differences between hydraulic heads of aquifers and surface water bodies are highest. This study therefore illustrates the impact of surface to subsurface water interactions in an urban context.